High density and connectivity of a MgB2 filament made using the internal magnesium diffusion technique. (22nd January 2016) - Kulich, M; Kováč, P; Hain, M; Rosová, A; Dobročka, E
Abstract: In order to allow precise and detailed physical studies of an MgB2 filament made by the internal magnesium diffusion process (IMD), a modified approach (MIMD) using a Mg tube filled with boron powder deformed into wire was introduced. The MIMD process allows easy extraction of the MgB2 filament after the final heat treatment and performance of four-probe resistive measurements and density estimation, which is not possible for standard IMD wires. The Rowell approach has been applied for the grain connectivity from R ( T ) data of extracted MgB2 for the first time. The filament's density has been estimated from the precise volume measured by x-ray micro-tomography and mass. The high connectivity and density of the MgB2 filament made by the diffusion process are discussed and compared with those of filaments made by other processes.